5G Network Security Challenges and Mitigation Techniques (International Journal of Engineering & Extended Technologies Research (IJEETR), 2022)
The advent of 5G networks promises unprecedented improvements in data speed, latency, and connectivity, enabling a new era of applications such as IoT, autonomous vehicles, and smart cities. However, the enhanced capabilities and architectural changes inherent to 5G introduce significant security challenges. These challenges stem from the network's increased complexity, virtualization, use of software-defined networking (SDN), network slicing, and expanded attack surface.This paper provides a detailed examination of the primary security threats facing 5G networks, including denial of service (DoS) attacks, data privacy breaches, man-in-the-middle attacks, and vulnerabilities in network slicing and edge computing. To address these challenges, the study reviews and analyzes current mitigation techniques such as robust encryption methods, authentication protocols, anomaly detection systems, blockchain integration, and AI-based intrusion detection systems. It also explores security frameworks that leverage the flexibility of 5G’s software-defined architecture to dynamically adapt to threats.A mixed research methodology combining qualitative literature review and quantitative analysis of recent 5G security incidents and experimental implementations forms the basis of this study. Key findings emphasize the necessity for a multi-layered security approach, combining traditional measures with advanced technologies like machine learning and blockchain to ensure confidentiality, integrity, and availability.The paper also presents a typical 5G security workflow highlighting vulnerability assessment, threat detection, mitigation, and continuous monitoring. Finally, advantages and disadvantages of current security measures are discussed, followed by insights into future work required to enhance the resilience of 5G networks against emerging cyber threats.
Keywords: 5G Networks; Network Security; Denial of Service; Network Slicing; Edge Computing; Intrusion Detection; Blockchain; AI Security; Virtualization; Mitigation Techniques